(untitled) (Psychology Travelogs, 2024)
The purpose of the article is to study the psychological features of advertisement consumers making influence on its personalization. The research methodology is based on the use of psychological and socio-psychological principles aimed at determining the psychological characteristics of consumers (using methods for determining personal value orientations of advertisement consumers, the level of extraversion and neuroticism), making it possible to determine the level of consumers’ dependence on advertising and its influence on them. The scientific novelty lies in the fact that, using the method of scientific literature analysis and the results of empirical research, an analysis of the influence of the consumer’s psychological characteristics on the personalization of advertising strategies was carried out. An advertising message becomes more effective if it is aimed at a certain segment of the target audience that has common characteristics. In the process of buying goods and services modern consumers demonstrate different behavioral patterns. A number of factors influence the process of making a purchase decision. The formation of an advertising campaign depends on the individual and typological characteristics of a person. Proven that under certain conditions, consumer behavior can be effectively managed, and marketing has a significant arsenal of tools for such management. Research is essential for creating advertisements and implementing advertising campaigns, helping identify the target audience, its characteristics and preferences, potential points of contact with advertising, and responses to advertising appeals. The utilization of consumer predispositions towards neuroticism and extraverted behavior in marketing contributes to the reinforcement and intensification of advertising dependence by influencing the emotional component of the consumer.